FUNDAMENTALS OF CRITICAL THINKING AND ITS METHODS IN PRESCHOOL EDUCATION (Journal of Multidisciplinary Sciences and Innovations, 2025)
This article examines the importance of critical thinking in early childhood education. It also highlights the importance of developing children's analytical and critical thinking skills at an early age, and discusses various methods and approaches that can assist in this process. The article also calls for more inclusive and innovative educational programs that will develop children's mental abilities and prepare them for successful lives in the modern world.